Corporate social responsibility : a comparative case study of three hospitality organisations. - Teo, Elyssa Zhi Xuan. (2011)
Corporate Social Responsibility (CSR) is a relatively new paradigm that companies are increasingly embracing, especially for businesses in Asia. With heightened global emphasis on sustainable tourism, owners, developers and especially operators in the hospitality industry are also making CSR a key driver of business growth. Policies and projects are being actively developed and implemented to help businesses improve not just their traditional bottom line; profit, but also the two other bottom lines, planet and profit; that can influence the overall sustainability of their businesses.